New statistical approach shows that hydroxy-methionine is noninferior to DL-Methionine in 35-day-old broiler chickens - Dolores I. Batonon-Alavo; Celsa Manceaux; Janet T. Wittes; Friedrich Rouffineau; Yves Mercier (Poultry Science, 2023)
ABSTRACT: The efficacy of a new molecule is assessed in the pharmaceutical industry through noninferiority tests to establish that it is not unacceptably less efficient than the reference. This method was proposed to compare DL-Methionine (DL-Met) as reference and DL-Hydroxy-Methionine (OH-Met) as alternative, in broiler chickens. The research hypothesized that OH-Met is inferior to DL-Met. Noninferiority margins were determined using 7 datasets comparing broiler growth response between a sulfur amino acid deficient and adequate diet from 0 to 35 d. The datasets were selected from the literature and internal records of the company. The noninferiority margins were then fixed as the largest loss of effect (inferiority) acceptable when OH-Met is compared to DL-Met. Three corn/soybean meal-based experimental treatments were offered to 4,200 chicks (35 replicates of 40 birds). Birds received from 0 to 35 d 1) a negative control diet deficient in Met and Cys; the negative control treatment supplemented on equimolar basis with 2) DL-Met or 3) OH-Met in amounts allowing to reach Aviagen Met+Cys recommendations. The three treatments were adequate in all other nutrients. Growth performance, which was analysed with one-way ANOVA, showed no significant difference between DL-Met and OH-Met. The supplemented treatments improved (P < 0.0001) the performance parameters compared to the negative control. The lower limits of the confidence intervals of the difference between means for the feed intake [-1.34; 1.41], body weight [-57.3; 9.8] and daily growth [-1.64; 0.28], did not exceed the noninferiority margins. This demonstrates that OH-Met was non-inferior to DL-Met.